Adoption of the Theory of Planned Behavior Approach in Exploring the Behavior of Induction Stove Assistance Recipients in Bali - Dewi, Sayu Ketut Sutrisna; Sukerayasa, I Wayan; Juliartini, Ketut; Wijaya, I Wayan Arta; Suputra, Gusti Alit; Harahap, Abriansyah (Transpublika Publisher, 2025)
Indonesia relies heavily on imported LPG with subsidies often benefiting higher-income groups. The government launched an energy transition program encouraging households to shift from LPG to induction stoves. This study investigates behavioral factors influencing induction stove adoption among assistance recipients in Bali Province, Indonesia's pilot project for the national initiative. Using the Theory of Planned Behavior (TPB) framework, a quantitative survey was conducted with 300 participants selected from 1,002 beneficiaries in Bali. Statistical analyses examined relationships among attitude toward behavior, subjective norms, perceived behavioral control, intention, and actual behavior. Attitude toward behavior, subjective norms, and perceived behavioral control significantly and positively influence adoption intention and behavior. Intention directly predicts actual induction stove use, validating TPB's applicability in this context. The TPB framework effectively explains household behavioral responses to government-led energy transition programs. However, findings are limited to Bali and require cautious generalization to other regions. This research provides policymakers valuable insights for designing effective behavioral interventions to accelerate national induction stove adoption and improve energy transition program outcomes.